SCIENTIFIC BASIS OF IMPROVING THE AUDIT OF FINANCIAL RESULTS IN BUSINESS ENTITIES - Jumayeva, Gulrukh Jurakulovna; Sultonova , Malika Otabek qizi (Educational Research in Universal Sciences, 2023)
This article describes the necessity, importance and theoretical aspects of the scientific basis of improving the audit of financial results in economic entities.